A Pre-Trial Standard Operation Procedure for Children in Conflict with Sharia Criminal Law in Malaysia - Yusof, Wafaa' binti (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Criminal offences committed by children in Malaysia do not only involve jurisdiction of the Child Act 2001 (Act 611), (Amendment 2016, A1511) but also jurisdiction of the states’ sharia criminal enactments and acts. Children are not exempted from being a perpetrator and contribute to increased rate in statistic of sharia crime throughout states in Malaysia. The social turmoil of humanity such as birth to an illegitimate child, abandoned babies were the impact from sharia criminal conduct of these children. Among factors for statistical increase on sharia crime by child offenders is due to ambiguity in legal provision regarding the position of child offender and pre-trial procedure for related sharia criminal matter. In fact, the flaws in the enforcement and implementation of pre-trial procedural laws against child offender are evident outcome from these legal ambiguities and the absence of a specific guideline in dealing with these perpetrators. Therefore, this paper discusses on justification on the importance to formulate a better and immediate alternative i.e. to establish a standard operating procedure (SOP) specifically for child offender at the pre-trial stage under the sharia criminal jurisdiction for the states in Malaysia. A pure legalistic study methodology of qualitative approach is used to produce this article. Data is gathered through library research and fieldwork study, which includes some semi-structured interviews with religious enforcers from the Department of Federal Territory Islamic Affairs (JAWI) and the Selangor Islamic Religious Department (JAIS) as respondents. The data were then conceptually and descriptively analyzed. This article presents a substantial justification to establish a pre-trial standard operating procedure for children in conflict with the states’ sharia criminal law in Malaysia.